2005
DOI: 10.1159/000085348
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Quality of Life after Thoracoabdominal Oesophageal Resection

Abstract: Background: The long-term functional outcome after thoracoabdominal resection has to be better evaluated. A study was performed to evaluate patients after a similar operation both in terms of physical function and health-related quality of life (HRQL). Methods: Eighteen patients were evaluated 2 years after a thoracoabdominal resection. Respiratory function, physical performance and range of motion in shoulder, thorax and spine were recorded. HQRL was assessed by EORTC QLQ-C30 (European Organization for Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies revealed that surgery is associated with decreased motor function in patients with oesophageal and colorectal cancers (Fagevik Olsén et al, 2005; Inoue et al, 2016; Sánchez‐Jiménez et al, 2015; Tatematsu et al, 2013). Therefore, given that surgery for pancreatic cancer is more invasive than that for colorectal cancer, motor function is also expected to decrease after pancreatectomy.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies revealed that surgery is associated with decreased motor function in patients with oesophageal and colorectal cancers (Fagevik Olsén et al, 2005; Inoue et al, 2016; Sánchez‐Jiménez et al, 2015; Tatematsu et al, 2013). Therefore, given that surgery for pancreatic cancer is more invasive than that for colorectal cancer, motor function is also expected to decrease after pancreatectomy.…”
Section: Introductionmentioning
confidence: 98%
“…It is of interest that both shoulders were equally affected. The explanation behind the high proportion of patients with pain in the left shoulder may be that, postoperatively, some patients increase their thoracic kyphosis (Fagevik Olse´n, Larsson, Hammerlid, and Lundell, 2005) with protruding shoulders, which may lead to impingement pain.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, a 2-year follow-up of the physical and functional status of 18 patients after thoracoabdominal esophageal resection found that they had a significantly reduced respiratory function compared to their preoperative status and that chest expansion was significantly impaired compared to age-and sex-matched controls (Fagevik Olse´n, Larsson, Hammerlid, and Lundell, 2005). A possible reason for this restrictive pattern may be the surgical trauma and persistent postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…These same authors concluded that because of the good sensitivity and specificity of the questionnaires, it was possible to detect small benefits associated with various forms of treatment [12]. In addition to this publication, other studies have also shown that the combined use of QLQ-C30 and QLQ-OES18 objectively reflects QoL in patients with esophageal cancer, which has been shown to be fundamental to ensure replicable results and to allow comparison between different populations [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 95%